A Theory of Outside Equity: Financing Multiple Projects - Spiros Bougheas; Tianxi Wang (Center for Economic Studies and ifo Institute (CESifo), 2019)
In the financial economics literature debt contracts provide efficient solutions for addressing managerial moral hazard problems. We analyze a model with multiple projects where the manager obtains private information about their quality after the contract with investors is agreed. The likelihood of success of each project depends on both its quality and the level of effort exerted on it by the manager. We find that, depending on the distribution of the quality shock, the optimal financial contract can be either debt or equity.
Keywords: G30; D86; 330; outside equity; financial contracts; principal agent model